Peran Ombudsman sebagai Moderator Kelembagaan Pemberdaya Modal Sosial Masyarakat - Hubeis, Musa; Saefuddin, Asep; Affandi, Joko; Suhartono (Universitas Brawijaya, Indonesia, 2015)
Ombudsman surveillance with additional unique role as of dispute handler, when it proceeds with isomorphism process within the school institutionalism, they will potentially raise positive relationships between schools and parents, and also the community at large. Based on new institutionalism literatures and organizational and sociological theorie,sthis study argues that several behavioral phenomenon imperically exist at every isomorphism process, i.e: initiation for diffusion, adoption of diffusion, partnership for adaptive governance, legitimacy endorsement, and being sustainability committed. This study aims to assess changes of those schools behavioral phenomenon, following the standardized socializations held by the Ombudsman of the Republik Indonesia (ORI). A survey was administratedto teachers and parents at 13 public elementary schools in five districs within Jakarta Metropolitan Area. Factor analysis, t-tests, ANOVAs and MRA were used. It revealed that ORI initiatives can somewhat subdue school bureaucracies, unfortunately it was also limitedly able to empower schools behavioral adoption and commitments. These findings imply thatORI initiatives can limitedly empowering schools in sustaining social capital, with specific handicaps hampering at every phase of isomorphism. What makes ORI initiatives less effective are being dicussed by exploring qualitative information emanated from in-depth interviews.